A unified decentralized framework for isolated interlinking converters of hybrid DC/AC microgrids - Li, Yue; Yang, Pengcheng; Peng, Yonggang; Weng, Chudi; Sun, Jing; Shen, Haijiang; Xia, Yanghong; Wei, Wei (Frontiers in Energy Research, 2023)
Due to the advantages of effectively integrating diversified loads and renewable sources, hybrid DC/AC microgrids have attracted the common attention of industry and academia. Meanwhile, with the increase of power electronic devices connected to the system, the complexity of the system increases, which puts forward higher requirements for galvanic isolation and intelligent control methods. To solve the above problems, this paper proposes a unified decentralized framework for Isolated Interlinking Converters (IICs) in hybrid DC/AC microgrids, including topology and control strategy. Firstly, in terms of topology, dual active bridge (DAB) is adopted to realize galvanic isolation and DC voltage conversion, which can facilitate the interconnection of DC microgrids or combined with VSC for the interconnection of DC and AC microgrids. Secondly, in terms of control strategy, a bidirectional voltage supporting control strategy is proposed for IICs, in which frequency and voltage are adopted as the indications to balance the power and strengthen the inertia interaction of microgrids. Furthermore, with the proposed control strategy, the voltage sources of different microgrids can share the power fluctuation, cooperatively. The stability of the proposed strategy is analyzed and the effectiveness is verified by several HIL experiments.